1996
DOI: 10.1002/elps.1150170424
|View full text |Cite
|
Sign up to set email alerts
|

Capillary zone electrophoresis in agarose gels using absorption imaging detection

Abstract: A simple home-built electrophoretic unit and a commercially available charge-coupled device (CCD) camera with image acquisition and analysis software were used to study the separation process in zone electrophoresis experiments in 4 cm long, round capillaries (inside diameter 0.2 mm). Several capillaries could be investigated simultaneously. The absorption imaging system was used not only to follow the course of the separation but also to study the interaction between biologically active substances (proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Another method was to fill the whole short capillary with the agrose gel, as in previous experiments [5]. Figure 3 shows the CE separation of the proteins in an agarose gel-filled 4 cm capillary with different injection times and different pH.…”
Section: Sample Injection and Ce Separation In A Gel-filled Short Capmentioning
confidence: 99%
See 4 more Smart Citations
“…Another method was to fill the whole short capillary with the agrose gel, as in previous experiments [5]. Figure 3 shows the CE separation of the proteins in an agarose gel-filled 4 cm capillary with different injection times and different pH.…”
Section: Sample Injection and Ce Separation In A Gel-filled Short Capmentioning
confidence: 99%
“…In previous experiments, it was demonstrated that wholecolumn imaging CE could be used for studying interaction between proteins and biologically active substances such as the detergent CTAB [5]. Here, protein binding or conjugation reaction between cytochrome c and surfactant SDS was investigated.…”
Section: Application Of Whole-column Imaging Ce With the Short Capillarymentioning
confidence: 99%
See 3 more Smart Citations